Police Role In The Effort Management And Control The Fight Between Youth In Making Public Order In The Blora Regency - Zaenul Arifin; Sukarmi Sukarmi (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
Group fights criminal acts defined as crimes of violence together as provided for in Article 170 of the Criminal Code. Data from Blora Regency police indicate that a fight between youth always the case in every year in the Blora Regency. This study aims to determine the role of the police in handling and overcoming a fight between youth, barriers and solutions in realizing the public order in Blora. The method used is the juridical sociological, descriptive analytical research specifications. The data used are primary data and secondary data, while the data collection method is field studies and literature. Using data analysis methods of qualitative analysis. The analysis used as knife crime prevention theory, theory and the theory of the role of law enforcement. The results showed that the role of the police in handling and overcoming a fight between youth in realizing the public order in Blora is through the efforts of non penal (preventive) and attempts penal (repressive). Barriers arising in the treatment and prevention of fights between youth to realize the public order in Blora is the number of police personnel limited, the police difficult to present witnesses so that not all the perpetrators can be arrested, the third party to interfere in the settlement of the problem, and the lack of awareness Public.Keywords: Role; National Police; Prevention; Fights Between Youth.